Evaluation of the Regulation and Response of Ocean Heat Content to Typhoons in the Northwest Pacific Based on GDCSM_Argo - Han Su; Chunling Zhang; Bo Shu; Lifu Fu (Journal of Marine Science and Engineering)
The Northwest Pacific is a source of strong typhoons accompanied by significantly changing ocean heat content (OHC). Based on the GDCSM_Argo dataset, all typhoons within twenty years are considered to explore the regulation of OHC between 0 and 2000 m with typhoons in this study. The results show a weak correlation between OHC and typhoons but a strong correlation between ocean heat content uptake anomaly (OHUA) and typhoons by wavelet, lag/lead, and EOF analyses. The energy reserve effect by the OHUA on typhoon generation is most significant at a 3-month lag. The OHUA above 300 m primarily influences typhoons’ temporal and spatial characteristics. On the other hand, typhoons enhance vertical transmission of OHC through entrainment. A modified version of the Richardson number (Rohc) is used for the characterization of the hydrostatic stability between ocean layers. The entrainment is particularly strong in the Northwest Pacific north of 20° N, where Rohc is between −0.2 and 0. The OHC below the mixed layer also responds to typhoon disturbances but transports less heat vertically than the near-surface layers. Our results suggest that GDCSM_Argo provides reliable data support for the study of the relationship between OHC and typhoons.